2021
DOI: 10.3390/jcm10163575
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders in Pediatric Migraine: A Questionnaire-Based Study

Abstract: There is a high comorbidity between migraine and sleep disorders (SD), with a mutual dependence between sleep and headache. This study aimed to analyze the relationship between headache features (migraine frequency and severity, migraine equivalents, use and efficacy of treatments) and sleep in pediatric migraine. Parents of children and adolescents with migraine completed the Children’s Sleep Habits Questionnaire (CSHQ) and the Epworth Sleepiness Scale for Children and Adolescents (ESS-CHAD) and answered ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…That is a mutual interaction. In a survey study conducted in a pediatric headache population of 140 patients, it was shown that sleep disturbance accompanied primary headache in 102 (72.9%) patients 22 . In addition, vertigo and vomiting were found to be statistically more common in the sleep disorder plus primary headache group.…”
Section: Discussionmentioning
confidence: 99%
“…That is a mutual interaction. In a survey study conducted in a pediatric headache population of 140 patients, it was shown that sleep disturbance accompanied primary headache in 102 (72.9%) patients 22 . In addition, vertigo and vomiting were found to be statistically more common in the sleep disorder plus primary headache group.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances are very common. About 25% of children suffer from them [ 24 ]. There is a mutual dependence between sleep and headaches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, poor sleep has a correlated state of migraine chronicity. On the other hand, migraine can be seen as a possible cause of sleep disturbances [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, targeting both disorders at the same time can significantly ameliorate the quality of life of patients (and their families) and reduce all symptoms. A recent study by our group (published after the period considered for this review article) aimed at analyzing the relationship between migraines and sleep in a wide sample of pediatric migraine patients [38]. The study was conducted by administering a standardized questionnaire (CSHQ) to patients presenting a definite diagnosis of migraine according to ICHD-3 criteria.…”
Section: Discussionmentioning
confidence: 99%